Automatic inspection of satsuma slices using a machine vision system - Blasco, José; Cubero, Sergio; Alegre, Santiago; Arias, R.; Alamar, María C.; Juste, Florentino; Moltó, Enrique (European Society of Agricultural Engineers, 2021)
Spain is one of the most important producer and exporter of fresh fruit in the world. Part of the Spanish production is commercialised as canned fruit, which represent 7.5% of the food industry and a market of about 4.200 million euros. However, the recent presence in the market of third countries with much lower production costs has reduced the Spanish canned fruit exports to the European Union in 50% in the last four years. This problem is particularly important in the case of satsuma slices, where only a few producers remain in Spain. A complete automation of the whole process is the only way for these enterprises to survive. Although most of the tasks have already been automated, the visual inspection at the end of the line is still performed by operators that separate manually the fruit in commercial categories.